2023
DOI: 10.16899/jcm.1251398
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Malachite Green-Based Photodynamic Therapy in Acute Myeloid Leukemia

Abstract: Aim: Acute myeloid leukemia (AML) is a disease characterized by relapse and treatment resistance in most patients. Therefore, there is a need for targeted therapies in AML. Photodynamic therapy (PDT) is a promising alternative for the treatment of malignant tumors. Also, PDT has the potential to be used individually or complementally in the treatment of leukemia. In this study, it was aimed to investigate possible the effect of malachite green (MG)-based PDT on acute myeloid leukemia cells. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…It is the subject of clinical research both as a treatment and as a complementary therapeutic procedure to other treatments (13). Although previous studies have shown that acute monocytic leukemia and chronic myeloid leukemia cells can be effectively killed using a variety of classical photosensitizers such as zinc phthalocyanine, Nile blue, 5-aminolevulinic acid (5-ALA), hypericin, malachite green, and Photolon ® (17)(18)(19)(20)(21)(22), the use of PDT It has received relatively less interest in the treatment of leukemia. The results of our study showed that malachite green-mediated PDT caused a significant decrease in the proliferation of HL-60 cells compared to both controls and malachite green.…”
Section: Discussionmentioning
confidence: 99%
“…It is the subject of clinical research both as a treatment and as a complementary therapeutic procedure to other treatments (13). Although previous studies have shown that acute monocytic leukemia and chronic myeloid leukemia cells can be effectively killed using a variety of classical photosensitizers such as zinc phthalocyanine, Nile blue, 5-aminolevulinic acid (5-ALA), hypericin, malachite green, and Photolon ® (17)(18)(19)(20)(21)(22), the use of PDT It has received relatively less interest in the treatment of leukemia. The results of our study showed that malachite green-mediated PDT caused a significant decrease in the proliferation of HL-60 cells compared to both controls and malachite green.…”
Section: Discussionmentioning
confidence: 99%